School Administration According to the Ten Royal Vitues of School Administrators Under the Secondary Educational Service Area Office Kanchanaburi - Somboondee, Kadsarin; Pumklom, Mitparnee (Journal of Graduate MCU KhonKaen Campus, 2023)
The objective of this study are 1) 1) to study administration according to the ten royal virtues of school administrators under the Secondary Educational Service Area Office Kanchanaburi. 2) to compare school administration according to the ten royal virtues of school administrators under the Secondary Educational Service Area Office Kanchanaburi classify by school size and work experience. The sample consisted of 308 teachers in school under the Secondary Educational Service Area Office Kanchanaburi obtained by stratified random sampling according to study area. The research instrument was a five-level rating scale questionnaire with content validity beteen 0.67- 1.00 and reliability of 0.93. The statistics used in the data analysis were percentage, mean, standard deviation, one-way ANOVA and testing the percentage different by Scheffé’s method. The statistical significance level was set at 0.5 The research results found that 1) School administration according to the ten royal virtues of school administrators under the Secondary Education Service Area Office Kanchanaburi, overall and in each individual aspect were at a high level, ranking in mean form high. 2) The comparison the school administration according to the ten royal virtues of school administrators under the Secondary Educational Service Area Office Kanchanaburi classify by school size, overall and in each individual aspect was no statistically significant difference.